Application of Nucleic Acid Reference Material for Rapid Detection of Cronobacter sakazakii (Cronobacter spp.) in Flammulina velutipes - Huandie Yang; Danyang Guo; Leilei Chen; Alexander Suvorov; Qingxin Zhou; Junhua Wang; Xiaofeng Gao; Jinyu Yang; Xiangyan Chen (Journal of Food Quality)
Cronobacter sakazakii (C. sakazakii) widely exists in the environment and is a common foodborne pathogenic microorganism. It can cause meningitis, bacteremia, and necrotizing enterocolitis in infants and elderly people with low immunity. Therefore, the development of the rapid detection method for foodborne pathogen C. sakazakii is very important for food safety control. This study has developed a kind of genomic nucleic acid reference material as a positive reference for the rapid detection of C. sakazakii in the edible fungus Flammulina velutipes. First, the genomic nucleic acids were extracted from the standard strain of C. sakazakii, and the nucleic acids were lyophilized. The uniformity test result of the lyophilized powder showed that there were no significant differences between samples. In short-term stability tests at 4°C and 37°C for 14 days, the properties of the nucleic acid reference material were good, and in long-term stability tests at 4°C and −20°C for 8 months, the samples are still stable. To verify the application of this nucleic acid reference material, it was used as a positive control template for PCR detection and applied to the rapid detection of C. sakazakii in F. velutipes. It was found that 13 of the 15 F. velutipes samples were positive for C. sakazakii. As far as we know, this is the first attempt to detect C. sakazakii in F. velutipes using the PCR method with nucleic acid reference material as the positive reference. This study is helpful in promoting the extensive and in-depth application of nucleic acid reference materials in foodborne pathogens detection.